2004
DOI: 10.1128/iai.72.5.2872-2878.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria Inhibit Nitric Oxide Synthase Recruitment to Phagosomes during Macrophage Infection

Abstract: Inducible nitric oxide synthase (iNOS) is a cytoplasmic protein responsible for the generation of nitric oxide (NO ⅐ ) in macrophages. In this work, we hypothesized that the intracellular localization of iNOS is significant for effective delivery of NO ⅐ to phagosomes containing ingested microorganisms. Using immunofluorescence microscopy and Western blot analysis, iNOS was shown to localize in the vicinity of phagosomes containing latex beads in stimulated macrophages. iNOS also localized to phagosomes contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 46 publications
5
89
1
4
Order By: Relevance
“…40 Mycobacterial phagosomes are also prevented from association with inducible nitric oxide synthase (iNOS), thereby limiting exposure to damaging nitrogen radicals. 146 This protective environment also prevents effective antigen processing of Mtb. 201 Our understanding of the mechanisms controlling phagosomal maturation is incomplete and controversial.…”
Section: Cell Biology Of Mtbmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Mycobacterial phagosomes are also prevented from association with inducible nitric oxide synthase (iNOS), thereby limiting exposure to damaging nitrogen radicals. 146 This protective environment also prevents effective antigen processing of Mtb. 201 Our understanding of the mechanisms controlling phagosomal maturation is incomplete and controversial.…”
Section: Cell Biology Of Mtbmentioning
confidence: 99%
“…65 Vacuolar proton ATPase, inducible nitric oxide synthase (iNOS), and natural resistance-associated membrane protein 1 (NRAMP1) are inhibited from associating with this phagosome, thereby avoiding pH reduction, reactive nitrogen intermediates (RNIs), and Fe 2þ /Mn 2þ starvation, respectively. 74,146,195 Phosphatidylinositol 3-phosphate (PI3P), a lipid involved in proper trafficking of lysosomal constituents to phagosomes, is also continuously eliminated from phagosomes containing live Mtb due to the hydrolytic activity of secreted lipid phosphatase, SapM. 211 Early endosomal autoantigen 1 (EEA1) and Hrs, both of which are trafficking molecules that associate with PI3P, are also prevented from associating with the Mtb phagosome.…”
mentioning
confidence: 99%
“…NO is reported to be microbicidal in vitro, which presumed to play a role in antimicrobial action. However, mycobacteria have developed the ability to resist ROI and RNI within the hostile environment of host phagocytes (32)(33)(34). In addition, NO represents as a crucial molecular signal, and we had previously reported that NO/iNOS-mediated regulation of proinflammatory gene expression involves multiple pathways in macrophages (18).…”
Section: Discussionmentioning
confidence: 99%
“…C'est ainsi que Salmonella enterica sérotype typhimurium inhibe l'assemblage de la NADPH oxydase, un complexe enzymatique à l'origine des dérivés bactéricides de l'oxygène [14]. De façon similaire, Mycobacterium bovis inhibe la formation de monoxyde d'azote (NO) et de ses dérivés bactéri-cides [15]. Une autre stratégie mise en place par les bactéries pathogènes pour survivre dans les macrophages consiste à inhiber la production des cytokines de la réponse M1.…”
Section: Infections Chroniques Perturbation De La Polarisation M1 Parunclassified